Growth pattern in tropical mangrove trees of Bunaken National Park, North Sulawesi, Indonesia - RIGNOLDA DJAMALUDDIN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Djamaluddin R. 2019. Growth pattern in tropical mangrove trees of Bunaken National Park, North Sulawesi, Indonesia. Biodiversitas 20: 1713-1720. Seasonal diameter growth patterns in mangrove are often related to rainfall, temperature and moisture regime. At any localities, specific environmental factors may influence growth rate of individual trees. I asked whether stem growth of tropical mangrove in BNP is constant over a year, and whether stem growth rates are different by sites, species, and trees of the same species. Dendrometer bands were installed on trees from twelve different sites in BNP to measure stem growth rates. Measurements were made at two months intervals from July 1999 to June 2001 and March 2014 to December 2016. Growth rates measured in trees at the twelve sites varied significantly from 0.83 ± 0.27 to 1.71 ± 0.31 mm month-1. Growth rates were higher on Sonneratia alba (1.65 ± 0.69 mm month-1), low on Rhizophora stylosa, Xylocarpus moluccensis, Avicennia marina, Ceriops tagal (0.82 ± 0.16, 0.82 ± 0.18, 0.85 ± 0.18, 0.88 ± 0.28 mm month-1, respectively), and medium on Rhizophora apiculata, Bruguiera parviflora, Bruguiera gymnorrhiza, Rhizophora mucronata (1.19 ± 0.16, 1.22 ± 0.69, 1.25 ± 0.49, 1.31 ± 0.22 mm month-1, respectively). Statistically, growth rates were higher in trees with initial girths more than 50 cm compared to trees with initial girth less than 50 cm on B. gymnorrhiza, C. tagal, and R. mucronata, but these were slower for R. apiculata and S. alba. Between individual trees in six species tested, the differences in diameter growth rate were statistically significant. Growth rates varied among different site conditions, and the effect of soil water salinity on these was significant at higher intertidal sites. Growth rates exhibited seasonal patterns, and these were correlated positively with rainfall and negatively with temperature. The effect of the 2015-2016 El Nino was significant on reduced growth rates.